KEMAMPUAN AWAL MATEMATIS MAHASISWA PROGRAM STUDI BUDIDAYA PERAIRAN - AMINULLAH AMINULLAH; SITI SOLIHUN (GANEC SWARA, 2023)
This study aims to describe the initial mathematical abilities of students of the Aquaculture Study Program, Faculty of Fisheries, University of 45 Mataram. This type of research is a survey with a quantitative descriptive approach. This research was conducted at University 45 Mataram in odd semesters in October 2022. The samples in this study were 31 students of the Aquaculture Study Program, Faculty of Fisheries, University of 45 Mataram. Retrieval of data in this study using test instruments and analyzed using descriptive statistical analysis.The results showed that 9 students or 29.03% of students were included in the category of low initial mathematical ability and 70.97% or 22 students were included in the category of very low initial mathematical ability. The average student score of 46.67 is included in the category of very low initial mathematical ability.